Implementasi Staffing dalam Upaya Peningkatkan Mutu SDM di Madrasah - Sony Eko Adisaputro; Solechan Solechan (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2025)
This study aims to analyse the implementation of staffing functions in improving the quality of human resources (HR) at Madrasah Aliyah Sunan Kalijaga Pakuncen. This study uses a descriptive qualitative approach with a single case study design. Data were collected through in-depth interviews, participant observation, and documentation of the foundation chairperson, madrasah principal, deputy principal for personnel, as well as teachers and educational staff. Data analysis was conducted interactively through reduction, presentation, and conclusion drawing with validity testing using source and method triangulation. The results showed that the implementation of staffing functions at MA Sunan Kalijaga Pakuncen included participatory human resource planning, internal recruitment and selection based on loyalty and competence, employee placement according to potential, and professional development through continuous training. Although there were obstacles in terms of technological mastery and the welfare of educators, the institution showed positive adaptation through internal training innovations and collaboration between madrasahs. These findings indicate that a value-based staffing system in Islamic educational institutions can serve as an integrative human resource management model that combines professionalism, spirituality, and institutional loyalty.